Antibiofilm and Antivirulence Properties of Indoles Against Serratia marcescens - Sethupathy, Sivasamy; Sathiyamoorthi, Ezhaveni; Kim, Yong-Guy; Lee, Jin-Hyung; Lee, Jintae (Frontiers in Microbiology, 2020)
Indole and its derivatives have been shown to interfere with the quorum sensing (QS) systems of a wide range of bacterial pathogens. While indole has been previously shown to inhibit QS in Serratia marcescens, the effects of various indole derivatives on QS, biofilm formation, and virulence of S. marcescens remain unexplored. Hence, in the present study, we investigated the effects of 51 indole derivatives on S. marcescens biofilm formation, QS, and virulence factor production. The results obtained revealed that several indole derivatives (3-indoleacetonitrile, 5-fluoroindole, 6-fluoroindole, 7-fluoroindole, 7-methylindole, 7-nitroindole, 5-iodoindole, 5-fluoro-2-methylindole, 2-methylindole-3-carboxaldehyde, and 5-methylindole) dose-dependently interfered with quorum sensing (QS) and suppressed prodigiosin production, biofilm formation, swimming motility, and swarming motility. Further assays showed 6-fluoroindole and 7-methylindole suppressed fimbria-mediated yeast agglutination, extracellular polymeric substance production, and secretions of virulence factors (e.g., proteases and lipases). QS assays on Chromobacterium violaceum CV026 confirmed that indole derivatives interfered with QS. The current results demonstrate the antibiofilm and antivirulence properties of indole derivatives and their potentials in applications targeting S. marcescens virulence.